Relação planta-animal em diferentes intensidades de pastejo com ovinos em azevém anual (Lolium multiflorum Lam.) - Roman, Juliano (2006)
This work aimed to evaluate the utilization of different grazing intensity on the productive and structural characteristics of pasture and on the ingestive behaviour and performance of sheep in continuous grazing. The treatment were different herbage masses (HM) in Italian ryegrass (Lolium multiflorum Lam.) pasture: LHM: 1000-1200 kg/ha of dry matter (DM); IHM: 1400-1600 kg/ha DM; HHM: 1800-2000 kg/ha DM. The experimental design was the randomly complete, with three treatments and two area replicates. The data were submitted at the regression analysis in function of HM observed in the experimental units: 1136.8, 1190.9, 1359.2, 1375, 1556 e 1739.1 kg/ha DM. The values of leaf lamina mass, pseudostem mass, forage allowance, leaf lamina allowance, sward height, pseudostem height, leaf lamina depth and average daily gain increased linearly with increase of HM (P<0.10). Quadratic effect (P<0.10) in herbage production, herbage losses and herbage disappearance were observed. The stocking rate (kg/ha of live weight and hoggets/ha) and bite rate decreased linearly with increase of HM (P<0.10). No HM effects (P>0.10) on the tiller population density, herbage daily accumulation rate, percentage of pasture utilization, herbage intake, grazing time, ruminating time, idle time, number of daily bite, bite mass, body condition score gain, live weight gain per area and conversion efficiency of forage in live weight were observed. Herbage mass varying among 1136.8 a 1739.1 hg/ha DM in Italian ryegrass pasture affect the herbage production and herbage losses, without influence in the percentage of pasture utilization, weight gain per area and conversion efficiency of forage in animal product. The main factor determining individual performance of animals is the leaf lamina layer depth